Turning the Tide on Poverty: Sustainability of community engagement in economically distressed communities. Issue 3 (26th May 2016) - Monroe, Pamela A.; Tyler-Mackey, Crystal; Dyk, Patricia Hyjer; Welborn, Rachel; Worthy, Sheri Lokken; Lowe, Catherine H.; Pickett, Natalie J.
Abstract: Turning the Tide on Poverty ("Tide") was a community engagement program implemented in rural communities in the southern United States seeking place-based solutions to poverty. Tide was structured to evolve and be sustained by local communities after formal support ended. Tide communities were visited a year or more after the end of the program to assess program sustainability. Key factors revealed through qualitative analysis to be important to program sustainability are discussed in the context of the Community Capitals Framework. The connection between Tide sustainability and the development of social capital in the communities is emphasized. Barriers to success and sustainability of Tide are discussed briefly.